Understanding Trauma Bonding through Saussurian Semiotics in Hozier's Cherry Wine - Octaviyanti, Adhillah Pratiwi; Sakinah, R. Myrna Nur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research examines the representation of trauma bonding in Hozier's song